Elderly People Balance Ability Based on Real-Time Training Model - Wang, Haotian (2023 International Conference on Electronics and Devices, Computational Science (ICEDCS), 2023)
Along with the decline of physical function, elderly people are more likely to fall than ordinary people. This paper established a comprehensive body balance assessment model for the elderly people through machine learning and principal component analysis. Then we use these three characteristics to classify the subjects blindly. In the process of classification, we use K-means clustering analysis method. we use the principal component analysis method to get the principal component factors of the assessment system of individual balance characteristics and the value of risk assessment. Finally reasonable suggestions are put forward for the elderly, such as taking part in more balancing exercises, strengthening muscle exercises and improving body shape.